2016
DOI: 10.3109/14767058.2016.1151870
|View full text |Cite
|
Sign up to set email alerts
|

Health outcomes of neonates with osteogenesis imperfecta: a cross-sectional study

Abstract: Our findings suggest that newborns with OI appear to be at high risk of skeletal disorders, preterm delivery and breech presentation. Younger maternal age and preterm delivery seem to be strong predictors of the need for NICU care. Our data suggest that pregnant women with OI younger than 20 years of age may benefit from added clinical supervision in anticipation of adverse effects on their child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…Yimgang et al assessed the at-birth health outcomes of 77 neonates with OI (60 with OI type I, 4 with OI type III, and 13 with OI type IV) and reported that 22% had respiratory complications in the neonatal period. 13 These data demonstrate that pulmonary disease is a major contributor to the morbidity and mortality in OI, especially in the more severe forms. To date, only six studies have systematically assessed pulmonary function using spirometry in individuals with OI.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Yimgang et al assessed the at-birth health outcomes of 77 neonates with OI (60 with OI type I, 4 with OI type III, and 13 with OI type IV) and reported that 22% had respiratory complications in the neonatal period. 13 These data demonstrate that pulmonary disease is a major contributor to the morbidity and mortality in OI, especially in the more severe forms. To date, only six studies have systematically assessed pulmonary function using spirometry in individuals with OI.…”
mentioning
confidence: 80%
“…The burden of pulmonary disease in OI patients can be observed even during the neonatal period. Yimgang et al assessed the at‐birth health outcomes of 77 neonates with OI (60 with OI type I, 4 with OI type III, and 13 with OI type IV) and reported that 22% had respiratory complications in the neonatal period . These data demonstrate that pulmonary disease is a major contributor to the morbidity and mortality in OI, especially in the more severe forms.…”
Section: Introductionmentioning
confidence: 99%
“…Developing data to better inform assessment and care for individuals with rare diseases is difficult; access to patients has been challenging and it can be hard to collect enough data to provide informed conclusions. One frequently recommended tool is a registry, an organized program for collection, storage, retrieval, and use of data on identifiable individuals that allows researchers to explore and define numerous health questions [2531]. Registries are particularly useful in the care of individuals with a rare disorder as they can help patients gain a broader insight into their health status regardless of whether they have access to a major clinical center.…”
Section: Introductionmentioning
confidence: 99%
“…Developing data to better inform assessment and care for individuals with rare diseases is difficult; patients can be challenging to access and it can be hard to collect enough data to provide informed conclusions. One frequently recommended tool is a registry [25][26][27][28][29][30][31]. Registries are particularly useful in the care of individuals with a rare disorder as they can help patients gain a broader insight into their health status regardless of whether they have access to a major clinical center.…”
Section: Disease Registries and The Osteogenesis Imperfecta Patient Pmentioning
confidence: 99%